Income disparities in Poland through the lens of economic geography - Jesús López-Rodríguez (Transformation, Integration and Globalization Economic Research (TIGER), 2012)
Second nature geography variables are very relevant in the explanation of income disparities across regions within countries and across countries. This paper uses the framework of the New Economic Geography to derive the structural equation which relates nominal wages with a distance weighted sum of incomes in the surrounding locations, the so called nominal wage equation. The estimation of this equation was carried out for 2000, 2004 and 2008 using regional data on Polish regions. The results of the analysis show that market access plays an important role in the explanation of income disparities in Poland. Moreover, the effects of market access have undergone several robustness tests to control for endogeneity issues linked to the construction of the market access variable and also to control for problems arising from shocks linked to spatially correlated but intertemporally uncorrelated omitted variables. Finally, using data for serveral years show us that the picture which emerges from the estimations is that the effect of market access on GDP per head levels is increasing over time leading to the conclusion that the core-periphery patterns in Poland have been reinforced ever since the first year of our analysis (2000).
Keywords: R11; R12; R13; R14; F12; F23; 330; New Economic Geography; Market Access; Income Disparities; Poland